The official (ISC)² SSCP CBK reference - Wills, Michael S. (Sybex, 2022)
The only official body of knowledge for SSCP--(ISC)2's popular credential for hands-on security professionals--fully revised and updated 2021 SSCP Exam Outline. Systems Security Certified Practitioner (SSCP) is an elite, hands-on cybersecurity certification that validates the technical skills to implement, monitor, and administer IT infrastructure using information security policies and procedures. SSCP certification--fully compliant with U.S. Department of Defense Directive 8140 and 8570 requirements--is valued throughout the IT security industry. The Official (ISC)2 SSCP CBK Reference is the only official Common Body of Knowledge (CBK) available for SSCP-level practitioners, exclusively from (ISC)2, the global leader in cybersecurity certification and training. This authoritative volume contains essential knowledge practitioners require on a regular basis. Accurate, up-to-date chapters provide in-depth coverage of the seven SSCP domains: Security Operations and Administration; Access Controls; Risk Identification, Monitoring and Analysis; Incident Response and Recovery; Cryptography; Network and Communications Security; and Systems and Application Security. The Official (ISC)2 SSCP CBK Reference is an essential resource for SSCP-level professionals, SSCP candidates and other practitioners involved in cybersecurity.